2006
DOI: 10.1097/01.blo.0000218738.69247.d8
|View full text |Cite
|
Sign up to set email alerts
|

Two-year Outcomes of Computed Tomography-based and Computed Tomography Free Navigation for Total Knee Arthroplasties

Abstract: Therapeutic Study, Level II. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…We identified 13 clinical series for comparison with the current navigation series (Table 2). Seven studies were prospective, randomized studies [1,7,23,25,28,29,34] and six were retrospective case-control series [2,12,17,[20][21][22]. We compared the characteristics of the patients and the radiographic results of the current case series with those in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…We identified 13 clinical series for comparison with the current navigation series (Table 2). Seven studies were prospective, randomized studies [1,7,23,25,28,29,34] and six were retrospective case-control series [2,12,17,[20][21][22]. We compared the characteristics of the patients and the radiographic results of the current case series with those in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…There is, however, little information about the clinical outcome [19][20][21][22]. This study was conducted to test the hypothesis that there are differences for subjective (WOMAC Score) as well as for objective (Knee Society Score, degree of flexion) criteria between CAS TKR and freehand TKR after 5.6-7.3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown its superiority regarding postoperative long leg alignment and component orientation [15,16,18,19]. Only a few studies focussed on the clinical outcome, and most of them evaluated only a short-term outcome [19][20][21][22]. We aimed to test the hypothesis that there is no difference either for subjective [Western Ontario and McMaster Universities (WOMAC) scores] or for objective (Knee Society Score, degree of flexion) criteria between CAS TKR and freehand TKR after 5.6-7.3 years.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies suggest navigation can increase the accuracy of component alignment, although it can also increase operative time and complications (Table 4) [6,8,10,17,18,[20][21][22]. A prospective, randomized study compared 60 conventional with 60 navigated TKAs and found the percentage of knees in which the mechanical axes deviated more than 3°was 20% and 1.7% in the two groups, respectively [8].…”
Section: Discussionmentioning
confidence: 99%